Experimental infection of a periodical cicada (Magicicada cassinii) with a parasitoid (Emblemasoma auditrix) of a proto-periodical cicada (Okanagana rimosa) - Lakes-Harlan, Reinhard (BMC Ecol, 2014)
BACKGROUND: The proto-periodical cicada Okanagana rimosa is subject to infection by the acoustically orientating parasitoid fly Emblemasoma auditrix. Furthermore, it is also the only known host of E. auditrix. Here we test the question, whether the highly adapted parasitoid can also infect other cicadas, like the periodical cicada (Magicicada cassinii) and which steps of the parasitization process can be completed. The experiments might also reveal whether such a parasitoid could hypothetically have been involved in the evolution of periodicity. RESULTS: The hearing threshold of E. auditrix matches with the spectrum of the calling song of M. cassinii, indicating potential host localization. Behaviourally, host localization is possible by the parasitoid as it approaches a loudspeaker broadcasting the buzz part of the calling song of M. cassinii. Magicicada cassinii is readily accepted as host and for host infection the parasitoid uses the same behavioural sequence as for its host O. rimosa. A larva is deposited into the timbal of the cicada. By contrast to O. rimosa the development of the fly larva is delayed and eventually suppressed in M. cassinii. CONCLUSIONS: The host range of E. auditrix is mainly determined by acoustic parameters. This filter is important, as other sensory cues seem not to be involved in the host selection process and larva will not develop in unsuited host. Although the recent parasitoid-host system seems to be stable in terms of coexistence of both species, an acoustically hunting parasitoid could have been a selective force during evolution of prime numbered periodicity in cicadas.